Design, synthesis, and bioactivity study on Lissodendrins B derivatives as PARP1 inhibitor. (1st September 2022) - Liu, Xinning; Wei, Xianfeng; Li, Xionghao; Yu, Rilei; Jiang, Tao; Zhao, Chenyang
Graphical abstract: Abstract: Poly(ADP-ribose) polymerase-1 (PARP1) is an enzyme that catalyzes the polymerization of ADP-ribose units to target proteins, and it is a potential target for anti-cancer drug discovery, especially for BRAC1/2 mutated tumors. In this study, a series of 2-aminoimidazole Lissodendrins B derivatives were designed, synthesized, and evaluated as PARP1 inhibitors. We found that compound D3 is better due to its PARP enzyme inhibitory activity and in vitro anti-cancer activity compared with other tested compounds. It could inhibit PARP1 enzymatic activity (IC50  = 17.46 µM) in the non-cell system and BRCA1-deficient HCC1937 and MDA-MB-436 cells growth (IC50  = 17.81 and 12.63 µM, respectively). Further study demonstrated that compound D3 inhibits tumor growth through multiple mechanisms, such as reduction of PARylation, accumulation of cellular DNA double-strand breaks, induction of G2/M cell cycle arrest, and subsequent apoptosis of BRCA1-deficient cells. Besides, the molecular docking study also confirmed that compound D3 could effectively occupy the active pocket of PARP1. Our findings provide a new skeleton structure for PARP1 inhibitor, and the results suggested that the compound D3 may serve as a potential lead compound to develop novel PARP1 inhibitors for cancer therapy.